Evidence that pericytes regulate aquaporin-4 polarization in mouse cortical astrocytes - Georg Andreas Gundersen; Gry Fluge Vindedal; Øivind Skare; Erlend A. Nagelhus (Brain Structure and Function, 2014)

The role of colonization in the dynamics of patchy populations of a cyclic vole species - Petter Glorvigen; Gry Gundersen; Harry P. Andreassen; Rolf A. Ims (Oecologia, 2013)

Territory ownership and familiarity status affect how much male root voles (Microtus oeconomus) invest in territory defence - Frank Rosell; Gry Gundersen; Jean-François Le Galliard (Behavioral Ecology and Sociobiology, 2008)

Individual and population level determinants of immigration success on local habitat patches: an experimental approach - Gry Gundersen; Harry P. Andreassen; Rolf A. Ims (Ecology Letters, 2002)
The effect of population density on immigration success of young root voles was studied in a factorial experiment where immigrants of three different types were translocated from donor populations to recipient habitat patches with experimentally manipulated population sizes. The different types of immigrants were: (1) residents, animals that had remained in their natal patch; (2) colonists, animals that already had successfully dispersed and settled in a new patch; and (3) transients, animals roaming around in a non‐habitable matrix area of the donor population. Generally, we found evidence for a negative density‐dependent immigration success in terms of survival, rate of sexual maturation and body growth rate. With respect to the survival rate, the degree of density dependence differed among the three immigrant types. Our findings are discussed with respect to the degree of rescue effect immigrants may have on a recipient population depending on population density, and also its relevance concerning translocation of individuals for conserving endangered populations.